Challenge of virus disease threats to ensuring sustained uptake of vitamin-A-rich sweetpotato in Africa - Kreuze, Jan F.; Cuéllar, Wilmer Jose; Low, Jan W. (Springer, 2021)
Orange-fleshed sweetpotatoes (OFSP) are a rich source of pro-vitamin A and can alleviate vitamin A deficiency in the developing world. In Africa, traditional varieties have been almost exclusively white-fleshed and introduction and breeding of orange-fleshed varieties into Africa has been severely hampered by virus diseases to which many varieties are susceptible. Breeding progress to generate resistant varieties has been slow due to rare and recessive occurrence of resistance in breeding populations. Production of virus-free seed is complicated by the fact that most sweetpotato viruses show no or only limited symptoms and very low virus concentrations when infected by individual viruses, making them difficult to detect. Even single infections can lead to significant yield losses, but when they combine severe disease complexes are generated, which can lead to total crop failure. Significant efforts have been made in characterizing and understanding virus interactions in sweetpotato over the last two decades to address this challenge; they are reviewed in this chapter. We also review the state of the art in detection of viruses in support of seed systems and breeding. We conclude with recommendations for the most urgent future research directions needed to address virus problems in sweetpotatoes.